Beach Volume Changes and Shoreline Sediment Properties at Eroded Area in Batu Pahat - Hayazi, Fitrah; Daud , Mohd Effendi; Mokhtar , Mardiha (Recent Trends in Civil Engineering and Built Environment, 2023)
Abstract: This research is about the correlation between the beach volume changes and shoreline sediment properties at eroded area in Batu Pahat. Pantai Punggur is selected as the study areas as it were assigned as eroded area due to critical erosion. The objective of this research is to study the beach volume changes and shoreline sediment properties thus correlate both parameters. The identification of beach volume changes is essential to evaluate the changes in volume at the coastal area whereas the study of shoreline sediment properties is compulsory to assess the beach condition. Shoreline sediment properties has been identified by carried out several testing on the soil sample whereas the analyzation of beach volume changes has been done by processing the aerial image in Pix4D Mapper and the analyzation of beach volume changes were carried out by Global Mapper Software. This research proves that the volume changes of the beach portray a significant change within one month interval. Based on the result obtained, the minimum and maximum average moisture content range between 70.1-122.6%, whereas the specific gravity data lies within 2.54 to 2.77. As for the particle size distribution, the percentage of sand is higher at HT (High Tide) and the percentage of silt is dominant at MT (Mid Tide) at each coastal zone. For the bulk density value, in relation with bulk density, the far the sampling point from the shoreline, the lower the bulk density. In summary, the data obtained shows that Zone A and E are more prone to erosion compared to the other zone. This proves that shoreline sediment properties have a correlation with beach volume changes that may resulted to an erosion condition.Keywords: Beach Volume, Volume Changes, Sediment Properties, Coastal Erosion.